(untitled) (Research, Society and Development, 2021)
The objective of this study was to analyze how the degree courses in Natural Sciences existing in Brazil have been conceiving the Youth and Adult Education (EJA) modality in the context of their Pedagogical Political Projects (PPPs). A documentary research was carried out, from PPPs referring to 72 courses reached, and data analysis took place through a qualitative approach, through the content analysis technique. The study was guided by the assumptions of interdisciplinarity, based on dialectical historical materialism, as we understand that undergraduates need human and emancipatory training to work with young and adult students, and be able to promote an education that transforms the social realities experienced by working class. Upon reading each document, three categories of analysis emerged: (1) Interdisciplinarity as principles of training and curriculum organization; (2) EJA as a professional field of activity for the egress; (3) Content of disciplines dealing with EJA. The results show that only 26 courses (36%) include EJA in their curricula and, of these, only nine (12.5% ​​of the total) propose, in the syllabuses, interdisciplinary actions for the teaching of Science committed to the social needs of the population, in order to provide a transformation of reality. It is concluded that most science degrees do not mind considering EJA as an important field of activity for graduates, needing to reorganize their curricula in order to recognize it as a teaching modality, as well as offering training aimed at building a fairer and more egalitarian society to the working class.